1990
DOI: 10.1002/pssa.2211170216
|View full text |Cite
|
Sign up to set email alerts
|

Photo- and Thermally Induced Change in the Volume of Thin Chalcogenide Films

Abstract: The volume expansion of chalcogenide layers is studied using the theory of bimetalic plates. The layers are evaporated on mica substrates and the bending of such composite during the raising of the temperature is measured. The differences between AsS, AsSe, and AsTe layers and the influence of irradiation and temperature are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…28 The integral has been performed over the FSDP, 0.3-2.1 Å Ϫ1 , 29 which gives ⌬D/DӍ1Ϯ0.5%, where the error is mainly due to sample-to-sample variation. This ratio is comparable to the experimental observations of the photoexpansion, ⌬V/VӍ0.5%, 8,9,12 despite the rough estimation procedure. In detail, we must take into account x-ray changes in the whole wave number, specifically in smaller wavenumber regions, the proportionality factor between ⌬V/V and ⌬D/D, 22 and so forth.…”
Section: A Origin Of the Photoexpansionsupporting
confidence: 88%
See 1 more Smart Citation
“…28 The integral has been performed over the FSDP, 0.3-2.1 Å Ϫ1 , 29 which gives ⌬D/DӍ1Ϯ0.5%, where the error is mainly due to sample-to-sample variation. This ratio is comparable to the experimental observations of the photoexpansion, ⌬V/VӍ0.5%, 8,9,12 despite the rough estimation procedure. In detail, we must take into account x-ray changes in the whole wave number, specifically in smaller wavenumber regions, the proportionality factor between ⌬V/V and ⌬D/D, 22 and so forth.…”
Section: A Origin Of the Photoexpansionsupporting
confidence: 88%
“…[8][9][10] The fractional expansion ⌬V/V is, for instance, about 0.5% in As 2 S 3 illuminated at room temperature. 8,9,11,12 In addition, Hisakuni and Tanaka have recently demonstrated that, upon illumination of subbandgap light, chalcogenide glasses exhibit more dramatic expansion, which can be referred to as ''giant photoexpansion.'' 13 For instance, As 2 S 3 exposed at room temperature to light emitted from a He-Ne laser exhibits volume expansions of ϳ5%, which can be utilized as microlenses.…”
Section: Introductionmentioning
confidence: 99%
“…The same process may occur in As 2 S 3 : photo-induced volume expansion of DV=V ¼ 0:5% has been demonstrated with bandgap illumination [25] and even ten times higher with subbandgap light [26]. This phenomenon has been discussed to be correlated to the widening of the interlayer distance [27].…”
Section: Resultsmentioning
confidence: 77%
“…Hence, the measurement of the absolute BE of electrons from a specified energy level is not reliable. The C 1s line from either adventitious carbon or intentionally added graphite powder on the surface has been widely used for charge referencing [19,20]. For this study, the adventitious carbon was used as a reference and the BE of the reference C 1s line was set as 284.6 eV.…”
Section: Methodsmentioning
confidence: 99%